English language needs of medical students in a public university in Malaysia - Wan Abd Malik, Wan Nur Syazwani (2017)
The majority of the medical schools in the world use English as the language for teaching and learning. English being the dominant language in medical education has posed a problem in English as a Second Language/ English as a Foreign Language (ESL/EFL) contexts, where proficiency in the English language among students whose first language is not English is lacking. Apart from having to deal with the demanding task of studying written content in English, medical students have to navigate their learning through various activities that require oral communication skills in English. This study sought to investigate the English language needs of medical students in a public university in Malaysia. Needs analysis was conducted using the English for Specific Purposes (ESP) framework, adopting Johns and Dudley- Evans Model (Ng, 2005; Johns & Dudley-Evans, 1980) that considers perception of student, language teacher and subject teacher. Specifically, the study examined the English language needs of medical students focusing on Reading, Listening, Writing and Speaking skills in their medical studies. The needs are analysed based on the overall English competency in medical activities and specific needs in each of the four language skills (Reading, Writing, Listening and Speaking). The needs are then ranked, and the perception from both medical students and lecturers are compared.Data were collected via questionnaires distributed to 226 medical students and 43 medical lecturers, interviews with 4 medical lecturers, and an observation of a teaching session between medical students and medical lecturers. The overall findings showed that there is urgency to address the students’ low competence in constructing grammatical sentences and using appropriate tenses. Speaking skills are perceived as the most important by both medical students and lecturers. In the ranking of the needs of students in specific medical activities, it is observed that the students are prioritising activities involving factual knowledge, while the lecturers’ priorities are more towards activities involving patient care. The results of this study can be used to contribute to the designing of an English language programme that addresses needs specific to the target group of medical students in Malaysia’s medical schools.